A simple validation and screening method for CRISPR/Cas9-mediated gene editing in mouse embryos to facilitate genetically modified mice production - Dawid Winiarczyk; Hossein Khodadadi; Paweł Leszczyński; Hiroaki Taniguchi (PLoS ONE, 2025)
Clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9 (CRISPR/Cas9) is a genome engineering method for generating site-specific editing in target genes in a variety of species. It is a common tool for generating mouse models of different diseases. However, detecting target modifications in mouse embryos can be time-consuming and expensive. Accordingly, developing a screening method to confirm gene modification may be useful. We propose herein an evaluation method (cleavage assay – CA) for CRISPR/Cas9-mediated gene editing in preimplantation mouse embryos that allows us to detect mutants efficiently and later on initiate in vivo production without the extensive number of samples needing to be sent for Sanger sequencing and animal usage. Our method is based on the inability of the RNP complex to recognize the target sequence after CRISPR-mediated genome editing due to modification of the target locus. It allows us to establish gene edited mice in a user-friendly fashion with a limited number of mice usage by confirming each step of CRISPR-mediated gene editing of mouse embryos and, therefore, can be considered as a supportive tool to existing procedures for verification of successful CRISPR/Cas9-mediated gene alterations in mouse embryos and further mutant production.